Prognostic role of elevated VEGF in sepsis: A systematic review and meta-analysis - Tang, A-ling; Peng, Yu; Shen, Mei-jia; Liu, Xiao-yu; Li, Shan; Xiong, Meng-chen; Gao, Nan; Hu, Tian-peng; Zhang, Guo-qiang (Frontiers in Physiology, 2022)
Background: The incidence and mortality of sepsis are increasing year by year, and there is still a lack of specific biomarkers to predict its prognosis. Prognostic value of vascular endothelial growth factor (VEGF) in predicting the severity and mortality of sepsis has been gradually discovered. Therefore, this systematic review and meta-analysis evaluated the prognostic value of VEGF in sepsis. Methods: An electronic search of the current literature was conducted through the PubMed, Embase, Web of Science, China National Knowledge Infrastructure and Cochrane Collaboration Central Register of Controlled Clinical Trials databases in March 2022. Observational studies, evaluating the impact of VEGF in sepsis outcomes (mortality and severity) are included in this meta-analysis. The risk of bias was assessed using the Newcastle-Ottawa scale (NOS). Sensitivity and publication bias analyses were also assessed. Meta-regression analysis were performed to identify the potential impact factors. Two authors independently performed literature-screening, risk of bias and data extraction. Result: The systematic literature search retrieved 1574 articles. In total, we included 20 studies in the qualitative analysis. Deceased and critically ill patients had higher baseline VEGF levels than survivors and non-severe patients (SMD=-0.77, 95% confidence intervals (CI) -1.17~-0.37, P=0.0002 and SMD=-0.41, 95%CI -0.6~-0.23, P=0.0002, respectively). The pooled sensitivity and specificity for VEGF predicts sepsis mortality were 0.79 [95%CI 0.67-0.87] and 0.76 (95% CI 0.63-0.85), respectively. the area under the SROC curve was 0.83(95%CI 0.81 ~ 0.87). Conclusion: This meta-analysis provides evidence that high VEGF are associated with poor clinical outcomes for patients diagnosed with sepsis. This study was recorded on PROSPERO, under the registration ID: CRD42022323079.